Usage of Some Agricultural By-products in the Removal of Some Heavy Metals from Industrial Wastewater - K. Badwy 2, Hanan F. Ahmad3, Hanan E. Osman1a*, Reham (Journal of Phytology, 2010)
Adsorption experiments were carried out using different biosorbent to adsorb some heavy metals from wastewater samples (industrial and domestic wastewater). In this work four agricultural residues rice hull, sawdust, sugarcane bagasse and wheat straw were examined as sorbent to remove Zn (II), Cd (II) and Fe (II) from wastewater samples. To modify their sorptive characteristics sorbents were treated with 0.1 M HNO3. Batch adsorption studies show that the modified rice hull and sawdust show a great ability for extracting metallic ions from wastewater samples as compared with the other sorbents. Sorption capacity of modified rice hull was significantly, in most cases, higher than the modified sawdust. In general, treated sawdust and rice hull sorbed the maximum amount of ions in all wastewater samples. In the column procedure, the removal percentage of Zn (II), Cd (II) and Fe (II) by modified rice hull and sawdust was significantly higher than the removal percentage of these metals by batch procedure. The results showed that the rice hull and sawdust were found to be an attractive low cost alternative for the treatment of wastewater. A good efficiency to remove toxic metal ions was achieved by usage of such by-product.